Hippea jasoniae sp nov and Hippea alviniae sp nov., thermoacidophilic members of the class Deltaproteobacteria isolated from deep-sea hydrothermal vent deposits - Flores, Gilberto E; Hunter, Ryan C; Liu, Yitai; Mets, Anchelique; Schouten, Stefan; Reysenbach, Anna-Louise (INTERNATIONAL JOURNAL OF SYSTEMATIC AND EVOLUTIONARY MICROBIOLOGY, 2012)
Thirteen novel, obligately anaerobic, thermoacidophilic bacteria were isolated from deep-sea hydrothermal vent sites. Four of the strains, designated EP5-r(T), KM1, Mar08-272r(T) and Mar08-368r, were selected for metabolic and physiological characterization. With the exception of strain EP5-r(T), all strains were short rods that grew between 40 and 72 degrees C, with optimal growth at 60-65 degrees C. Strain EP5-r(T) was more ovoid in shape and grew between 45 and 75 degrees C, with optimum growth at 60 degrees C. The pH range for growth of all the isolates was between pH 3.5 and 5.5 (optimum pH 4.5 to 5.0). Strain Mar08-272r(T) could only grow up to pH 5.0. Elemental sulfur was required for heterotrophic growth on acetate, succinate, Casamino acids and yeast extract. Strains EP5-r(T), Mar08-272r(T) and Mar08-368r could also use fumarate, while strains EP5-r(T), KM1 and Mar08-272r(T) could also use propionate. All isolates were able to grow chemolithotrophically on H-2, CO2, sulfur and vitamins. Phylogenetic analysis of 16S rRNA gene sequences placed all isolates within the family Desulfurellaceae of the class Deltaproteobacteria, with the closest cultured relative being Hippea maritima MH2T (similar to 95-98{%} gene sequence similarity). Phylogenetic analysis also identified several isolates with at least one intervening sequence within the 16S rRNA gene. The genomic DNA G+C contents of strains EP5-r(T), KM1, Mar08-272r(T) and Mar08-368r were 37.1, 42.0, 35.6 and 37.9 mol{%}, respectively. The new isolates differed most significantly from H. maritima MH2T in their phylogenetic placement and in that they were obligate thermoacidophiles. Based on these phylogenetic and phenotypic properties, the following two novel species are proposed: Hippea jasoniae sp. nov. (type strain Mar08-272r(T)=DSM 24585(T)=OCM 985(T)) and Hippea alviniae sp. nov. (type strain EP5-r(T)=DSM 24586(T)=OCM 986(T)).
Keywords: HOV Alvin (Human Occupied Vehicle); ROV Jason (Remotely Operated Vehicle)